Behavioural profile of newly-captured stray dogs and the efficacy of dog appeasing pheromone in reducing post-capture stress and fear-related behaviours - Manikam, Purshyla; Dhaliwal, Gurmeet Kaur; Sugnaseelan, Sumita (2012)
This study aimed to outline the behavioural profile of stray dogs post capture, as well as to determine the efficacy of Dog Appeasing Pheromone (DAP) in reducingpost-capture stress and fear-related behaviours. The behaviour of 17 stray dogs was observed using instantaneous scan sampling for 3 days after being caught from the streets with loop snares, as is the current practice for stray dog control in Malaysia. Following capture, 7 dogs were kept in kennels fitted with DAP diffusers, while 10 were untreated. The untreated adult stray dogs exhibited persistently high coping behaviour for 3 hours post-capture, followed by decreased panting and increased ‘sternal recumbency with head down’ by Day 2. Coping behaviour peaked during kennel cleaning. Significantly higher frequency of maintenance behaviour, whimpering, and ‘exit squeeze’ was observed in puppies compared to adult dogs. DAP-treated dogs had significantly decreased panting and ‘sternal recumbency with head low’, as well as increased standing and ‘sitting with head low’, as compared to the untreated group. Dogs treated with DAP also had an earlier decline in coping behaviour post-capture. This suggests that DAP is a useful tool in reducing some behavioural indicators of stress in dogs post-capture.